Effectiveness of environmental standards in shaping trade volume: Evidence from non-oil advanced economies (1990–2021) - Abderraouf, Messaoudi; Touati, Hichem; Tamma, Samir (International journal of economic perspectives, 2025)
This study aims to measure the impact of environmental standards and requirements on trade volume during the period (1990–2021), through a case study of non-oil advanced countries, namely: Belgium, Denmark, France, Germany, and Italy. A model was developed to assess the effect of environmental standards and requirements, expressed by two variables—environmental policy stringency and environmental taxes—on trade volume. To achieve the study objectives, a set of econometric approaches, methods, and tests were applied, including the unit root test for time series. For the empirical analysis, panel data were employed using the Mean Group (MG) and Pooled Mean Group (PMG) estimators, both of which are methods for cointegration estimation in the context of non-stationary panel data. The study concluded that there is a positive effect of environmental policy stringency on trade volume in non-oil countries, and a direct relationship between environmental taxes and trade volume. In other words, higher environmental taxes and stricter environmental policies lead to changes in trade volume that enhance domestic production and its international competitiveness, increase export competitiveness, and facilitate penetration of international markets and acquisition of market shares. This, in turn, strengthens the role of exports in shaping trade volume.